2012
DOI: 10.3844/jssp.2012.472.478
|View full text |Cite
|
Sign up to set email alerts
|

Employability Skill Acquisition among Malaysian Community College Students

Abstract: Abstract:The objective of this study was to assess the acquisition of employability skills among Malaysian community college students. The sample size of the present study 325 students selected randomly. Employability skills were measured using an instrument developed by the Secretary's Commission on Achieving Necessary Skills (SCANS). The overall mean of employability skills among community college students was 3.63 (S.D. = 0.47). Thus, we consider the employability skills of community college students to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 6 publications
(9 reference statements)
3
6
1
Order By: Relevance
“…This finding contradicts those of Omar et al (2012) who found that industrial training did not necessarily helps students acquire soft skills, though it did helps students increase their technical skills. However, finding by C. Paisey and N. Paisey (2010) shows that experience gained through work placement successfully develops a range of transferable personal skills.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…This finding contradicts those of Omar et al (2012) who found that industrial training did not necessarily helps students acquire soft skills, though it did helps students increase their technical skills. However, finding by C. Paisey and N. Paisey (2010) shows that experience gained through work placement successfully develops a range of transferable personal skills.…”
Section: Discussioncontrasting
confidence: 94%
“…= 0.55) than those obtained by Rohana and almost similar with the result of the present study. Another study by Omar, Bakar, and Rashid (2012) using community college students also confirmed the moderate findings in their sample (Mean = 3.63, SD. = 0.47).…”
Section: Discussionsupporting
confidence: 63%
“…Jurnal Pendidikan Indonesia Gemilang Vol.3, No.1, 2023, pp. 97-102 e-ISSN 2809 101 employability skills in students will certainly help them in working, surviving in work and getting a better career than individuals who do not master employability skills (Shyamalee, Wickramasinghe, & Dissanayake, 2013;Adi & Ni'am, 2013;Omar, Bakar, & Rashid, 2012;Yusoff, Omar, Zaharim, Mohamed, & Muhamad, 2012;Zaharim, et al, 2010). The results of other studies also show that employability skills can determine a person's success in carrying out their work (Burgaz, 2008;Kwok, 2003).…”
Section: Before Treatment After Treatmentmentioning
confidence: 99%
“…Hidayat et al (2019) stated that it is important to instill the soft skills values which includes communication, honesty, discipline, self-awareness, motivation, teamwork, leadership, adaptation, and problem-solving. On the other hand, soft skills or employability skills should be emphasized at different educational levels, especially at the training institutions to accelerate graduates and school leavers employed by the industrial players (Omar et al, 2012).…”
Section: The Character Of Vhs Graduatesmentioning
confidence: 99%
“…This is consistent with research by Hidayat et al (2019), which states that VHS graduates need to have certified supporting competencies that include computer skills, language skills (English and Mandarin), and other aspects of soft skills. The aforementioned skills can be practiced via informal and formal learning environments as those skills are related to day-to-day matters, for instance, having a conversation with different people and dealing with assignments (Omar et al, 2012).…”
Section: Vhs Graduates' Workforce Skillsmentioning
confidence: 99%